A study of the job training needs of the support staff in the six Kansas Board of Regents university libraries - Zhang, ShaLi (Kansas State University, 2005)
The purpose of this study was to learn the perceived training needs of the support staff in the six Kansas Board of Regents’ (KBOR) university libraries. Based on data from field and pilot studies and advice from an expert panel, a survey instrument was designed to assess library support staff’s perceptions of their train needs on computer skills, interpersonal skills, supervision/management skills, important library/organizational support, helpful training delivery methods, and training sources. The survey instrument was administered to the entire 167 support staff in the six KBOR university libraries, with a return rate of 83 percent achieved through two mailings and two postcard reminders. Quantitative data from the responses to closed-ended questions were analyzed through descriptive measures and one-way multivariate analysis of variance (MANOVA). Qualitative approaches to code answers from open-ended questions were utilized in order to allow stakeholder themes to emerge. Quantitative analyses indicated that the respondents viewed the most important training topics for each area of the study to be: database searching and MS Office suites for computer skills; working with difficult people and managing priorities for interpersonal skills; training new employees and supervising student employees for supervision/management skills; being supplied with appropriate software, release time, and technical support were viewed as the most important library support that would help their training. The respondents perceived classroom instruction with a teacher and interactive classroom discussions as being the most helpful delivery methods. The respondents considered in-house trainers, supervisors, and co-workers as being the most helpful training sources. A series of MANOVA tests were conducted on the six areas of the study. At the alpha = .05 level, statistically significant differences were found in the respondents’ perceptions of training needs on computer skills measured by their work units, supervision/management skills measured by their work units and level of job responsibilities, the respondents’ perceptions of important library/organizational support measured by their total years in the library filed and age range, and the respondents’ perceptions of helpful training sources measured by their total years at current positions. Qualitative analyses provided 314 units of information on 32 themes on additional training topics, library/organizational support, delivery methods, and training sources. The top 10 themes were related to “Software programs,” “Windows operating systems,” “Release time,” “Supervisor/management support,” “Relevance/applicable training,” “Promotion/opportunities,” “Training for motivation,” “Classroom with feedback,” “Training materials,” and “One-on-one and in-house training.” Based on the findings, summaries, and conclusions of this study, the researcher made recommendations for further study that focuses on job training needs of support staff at university libraries, including a broader scope of training topics, motivating factors, the perceptions of library administrators on the support staff’s training needs, training needs on supervision/management for non-supervision support staff, differing views on library/organizational support, different training delivery methods, etc.
Keywords: Adult and continuing education; Library science; Univeristy libraries; Computer skills; Training for support staff; Technology; Library Science (0399); Higher Education (0745); Adult and Continuing Education (0516)